Knowledge and Skills as Main Predictors in Nurse Disaster Preparedness - Ilfa Khairina; Nelwati Nelwati; Esthika Ariany Maisa; Dally Rahman; Aree Sanee (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Information about the factors that affect nurses' preparedness in hospitals is currently inadequate. Therefore, knowing the predictors that most influence nurse preparedness for disasters is vital. This study aims to determine the predictor factors that affect the disaster preparedness of nurses at the Padang Hospital. A cross-sectional design method has been used in this study. The selection of respondents was carried out using a purposive sampling technique. The criteria were nurses involved as a team for natural and non-natural disasters, COVID-19, in two public hospitals in Padang. The data collection used the Disaster Preparedness Evaluation Tools, Self-Regulation Scale, and Practice Environment Scale-Nursing Work Index. Analysis of the data in this study using the Structural Equation Model. The findings showed that knowledge and skills in disaster preparedness significantly affect disaster preparedness with a p-value of 0.001. Overall, these factors explain 87% of the total variance. Optimizing knowledge and skills in disaster management can improve nurses' preparedness in disasters. The hospital can make structured programs and manage disaster mitigation team resources to increase disaster preparedness.